The hundred years' war on Palestine : a history of settler colonialism and resistance, 1917-2017 - Khalidi, Rashid (Metropolitan Books, Henry Holt and Company, 2020)
A history of the Israeli/Palestinian conflict told from the Palestinian perspective, arguing the period since the Balfour Declaration of 1917 has amounted to a hundred years of colonial war against the Palestinians.